The health consequences of cultural consonance : cultural dimensions of lifestyle, social support, an arterial blood pressure in an African american comunity. - Dressler, William W. (American Antropological Association, 2000)
Cultural dimensions of health and behavior have been difficult to study because of limited theoretical and methodological models linking the cultural, the individual, and the biological. We employ a cognitive theory of culture to understand culture and health in an African American community in the southern United States. First, cultural consensus analysis is used to test for shared cultural models of lifestyles and social supports within the community. Then, the theoretical and operational construct of "cultural consonance" is used to assess the degree to which individuals behave in a way consistent with cultural models. Findings indicate that cultural consonance in lifestyle and social support combine synergistically in association with blood pressure. These associations of cultural consonance and health are not altered by taking into account a variety of other variables, indicating an independent association of cultural dimensions of behavior with health status. Implications of these results for culture theory are discussed.